2016
DOI: 10.1080/09602011.2016.1176934
|View full text |Cite
|
Sign up to set email alerts
|

Validation and clinical utility of the executive function performance test in persons with traumatic brain injury

Abstract: This study examined the relationships between the Executive Function Performance Test (EFPT), the NIH Toolbox Cognitive Function tests, and neuropsychological executive function measures in 182 persons with traumatic brain injury (TBI) and 46 controls to evaluate construct, discriminant, and predictive validity. Construct validity: There were moderate correlations between the EFPT and the NIH Toolbox Crystallized (r = -.479), Fluid Tests (r = -.420), and Total Composite Scores (r = -.496). Discriminant validit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…Executive Function Performance Test (EFPT) -Bill Paying subtest [42], [43]. A performance-based assessment of EF.…”
Section: Assessmentsmentioning
confidence: 99%
“…Executive Function Performance Test (EFPT) -Bill Paying subtest [42], [43]. A performance-based assessment of EF.…”
Section: Assessmentsmentioning
confidence: 99%
“…Fit of each of the measures to a unidimensional CFA model and to the GRM IRT model provide evidence of the internal or structural validity of the measures. Evidence supporting construct validity was reported by Baum et al, 59 who found that participants with severe TBI who had higher scores on a functional performance test also had higher TBI-QOL Independence scores. Future work evaluating changes in scores over time or in response to interventions designed to improve independence would provide further support for the validity of the TBI-QOL Independence and Asking for Help measures.…”
Section: Validation and Future Directionsmentioning
confidence: 56%
“…The term ecological validity is used here to refer to generalisability (veridicality, or the extent to which assessment results relate to and/or predict behaviours outside the test environment) and representativeness (verisimilitude, or the degree to which assessments resemble everyday life contexts in which the behaviours will be needed). While not the original meaning of the term (see Burgess et al, 2006 for discussion andBaum et al, 2017), it is the meaning that is now in general use.…”
Section: Introductionmentioning
confidence: 99%
“…Additional content on two of the measures cited by Poncet et al is provided in three papers in this volume. Baum et al (2017) show data on the validity and clinical utility of Executive Function Performance Test in a large sample of adults with traumatic brain injury. Clark, Anderson, Nalder, Arshad and Dawson (2017) and Nalder, Clark, Anderson and Dawson (2017) add to a growing literature on the psychometric characteristics and clinical utility data of the Multiple Errands Test (MET).…”
Section: Introductionmentioning
confidence: 99%